Population Consultations: The Experience in Guinea - Mohammed Lamine Yansané (World Health & Population, 2017)
Dr. Yansané is the senior policy advisor to the Minister of Health in Guinea and the former Head of the Minister’s Office and former Secretary General, Health. He has been instrumental in advocating for and co-organizing the États Généraux de la Santé in Guinea in 2014. His perspective is clearly one of a policy and decision-maker who has a particular interest in bringing population views, needs and expertise into the policy-making process in the hope that it will lead to improved buy-in of the policy and better implementation. Dr. Yansané was requested to provide input on the utility value of population consultations in his country and the added value from his perspective of more international debate on deliberative democracy in the health sector.
Keywords: Population consultation, WHO, policy development, health reforms, Guinea